ZnO–SnO2 nanocubes for fluorescence sensing and dye degradation applications. Issue 5 (1st March 2021) - Kumar, Ramesh; Umar, Ahmad; Kumar, Rajesh; Chauhan, M.S.; Al-Hadeethi, Yas
Abstract: ZnO–SnO2 nanocubes were used as promising material for efficient sensing of p-nitrophenol and faster photocatalytic degradations of dyes like methyl orange (MO), methylene Blue (MB) and acid orange 74 (AO74). ZnO–SnO2 nanocubes were prepared by the facile solution process at 50 °C using Zn(NO3 )2 ·6H2 O and SnCl2 ·2H2 O as a precursor in the presence of ethylenediammine. The synthesized material was examined for its morphological, structural, crystalline, optical, vibrational, and compositional studies by using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and photoluminescence spectroscopy. FESEM studies revealed the formation of well-defined ZnO–SnO2 nanocubes where the structural examinations revealed the formation of a crystalline tetragonal rutile phase for SnO2 with some crystal sites doped with Zn. The as-synthesized nanocubes were explored for their photocatalytic activities towards three different dye viz. MO, MB, and AO74. Practically, complete degradation of AO74 was seen within 4 minutes of photo-irradiation in the presence of 0.05 g ZnO–SnO2 nanocubes. However, 97.17% and 41.63% degradations were observed for MB and MO within 15 and 60 minutes, respectively. All the dye degradation processes followed the pseudo-first-order kinetic model. Moreover, the as-synthesized nanocubes were utilized to fabricate highly sensitive and selective fluorescent chemical sensor for the detection of p-nitrophenol (PNP). ZnO–SnO2 nanocubes showed a very low detection limit of 4.09 μM for the detection of PNP as calculated according to the 3σ IUPAC criteria. Further, the as-synthesized ZnO–SnO2 nanotubes were found to be highly selective for p-nitrophenol as compared to the other two isomers.